PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN ANGGOTA DI KJKS BMT RIZQONA IKABU TAMBAKBERAS JOMBANG - Wisnu Mahendri; Ita Rahmawati; Akhmad Taqiyuddin (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study is to describe: the influence of service quality on the decision of KJKS BMT RIZQONA TAMBAKBERAS JOMBANG members. This type of research uses a descriptive approach with a quantitative approach. Data collection techniques using the commissioner, respondents were members of KJKS BMT RIZQONA, amounting to 100 people, sampling techniques using non-Probability. In this study an R2 of 0.644 was obtained, which means that the variable quality of service only contributed an influence of 64.4%. Based on the results of the t test obtained t value of 13.332 with a significance level of 0.000 less than 0.05. Then Ho refused Ha accepted, that the quality of service significantly influences the decision of KJKS BMT RIZQUNA TAMBAKBERAS JOMBANG members. Keywords: Service Quality, Member Decision